Práticas educativas e integralidade na saúde da família: um estudo etnográfico - Oliveira, Neuma Lucia de (2013)
Primary Health Care, especially in the family health strategy, it is expected that the joint assistance and actions of health promotion. The Ministry of health (BRAZIL, 2007) defines health education as an eyeshadow strategy of prevention and health promotion, based on reflective practices, which allow the user to their condition of historical, social and political subject, under the vision of an expanded clinic on the part of health professionals. In this sense, there are guidelines for it professionals to develop educational activities and that they can interfere in the health/disease process of the population, with a view to the development of autonomy of the subject. This research had as objective to understand in the light of the integrality of the care, as is the production of health education practices, within the framework of the family health strategy from ethnographic study in a family health unit (USF). The location of the research was the unit of USF Felipe Camarão II in West Health District, in the city of Natal, RN, Brazil, selected from preliminary mapping of educational practices deployed in units of health of the family of this municipality, based on criteria such as time-to-deployment of USF and sustainability of existing actions. Immersion in the field consisted of participant observation with journaling, held during the period of August 2012 to January 2013, in which she accompanied team work processes in clinical-welfare actions on the USF, in households and in educational activities of group character. The results presented in ethnographic description were analyzed based on the axes proposed by Ayres (2009) for identification of integrality in health practices:the axis of the needs; the axis of the purposes; the joint axis; and the axis of the interactionsThe evidence described from observation point the presence of each axle up health education practices developed by the teams, even incipient form, namely: articulation and appreciation of knowledge and practices of popular culture with local initiatives (Pastoril do Peixe Boi Encantado, Auto de Natal e Grupo Terapia e Arte); Clinical integration with health promotion actions and coordination of multidisciplinary knowledge, with professional-user link (course for pregnant women). However, a few challenges were identified to be faced in order to move forward in these practices in integral care: the need to break with the fragmentation of actions; strengthening teamwork; need for greater sustainability policy of collective actions; intersectoral work aimed at a better role of the State in the face of the health-disease process, adding to the action of individuals.The analysis produced from observation of the processes experienced indicates the need for a better recognition of local managers that actions similar to those that occur in the USF Felipe Camarão II enable advances in completeness as allows inclusion of actors involved in the processes of health work, and stimulate participation and shared responsibility in the fight for health-disease situations